Islam and Christian Perspective Toward Global Religious Education in Indonesia - Ahmad Hermawan (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Globalization challenges Muslims and Christians in developing religious education in Indonesia. The problem of globalization has attacked the spiritual values of education. The output of religious teachings has recently shifted from the primary goal, namely the goal of education, because the education system is religiously oriented. Intolerance, corruption, human rights violations and all forms of moral decay that the Indonesian nation faces are manifestations of the minimal results of the cultivation of religious education in Indonesia. To fill this gap, this study tries to analyze and solve the problem of religious education from both an Islamic and a Christian perspective. The research used in this article is a discourse analysis method by comparing Islamic religious education and Christian religious education in Indonesia. Cooperation between the government and religious education is needed to develop religious education in Indonesia's global era. It requires integration between religious values and the positive values of globalization. Inter-religious and inter-religious dialogue must be included as part of religious education. Religious and educational institutions must be separated from commercialization, and cooperation between Christian and Islamic institutions. The Ministry of religious affairs as the higher authority in religious education, have to build mutual cooperation between the Islamic institution of religious education and the Christian Institution of religious education to support dialogue and sharing in term of harmonization.